Operacionalização dos objetivos educacionais nos cursos de engenharia - Filizzola, Therezinha (1979)
Several strategies can be adapted for the attainment of the purposes of a subject in school curriculum. The strategy of teaching by operationalized objectives is based on the principle of stating the educational objectives in terms of the expected performance of the pupil, and in stating the minimum standards for this performance. The implementation of a course of studies planned with the strategy of operationalized objectives should be made with full knowledge, by the students, of the performance that they are expected to master. This course of studies should be the basis for the planning of all the school activities of the teacher and of the pupils. This empirical research indicates that, in terms of main effect, the strategy of teaching by operationalized objectives is slightly more effective than the traditional strategy of teaching . This research, the purpose of wich was to compare the effectiveness of three teaching strategies - traditional teaching, and the teaching based on operationalized educational objectives, with and without freedom of choice by the students of some of the educational objectives - resulted, in three classes where each of those strategies was adopted, the indexes of effectiveness of 5,63 for the traditional strategy, 7,48 for the strategy of teaching with operationalized objectives without freedom of choice, and 7,29 for the strategy of teaching with operationalized objectives with freedom of choice of objectives. Strong second order interaction effects were detected between several variables analyzed: Variation of the LeveI of Knowledge of the subject and Entrance Examination Performance, Socio-Economical and Cultural status, and Attendance. The results indicate that the strategy with operationalized objectives is significantly superior to traditional teaching for several of the categories into which the groups split when classified according to these variables.